Role of porins in intrinsic antibiotic resistance of Pseudomonas cepacia. - Parr, T R (1987)
The measured outer membrane permeability of Pseudomonas cepacia to the beta-lactam nitrocefin was low: approximately 10 times less than that of Escherichia coli and comparable to that of Pseudomonas aeruginosa. The purified P. cepacia porin demonstrated an average single channel conductance in 1 M KCl of 0.23 nS.